Dari Krisis Ruang Publik ke Kemitraan Intersektoral: Studi Kasus di RPTRA Kalijodo, Jakarta - Rakhmat Hidayat; Ayuningtyas Suciani Utari (Institut Teknologi Sepuluh Nopember, 2018)
This article discusses about the partnership between stakeholders in managingChild-Friendly Integrated Public Space (RPTRA) in Kalijodo, West Jakarta.Researchers use the Child-Friendy Integrated Public Space concepts,stakeholder concepts, and partnership stakeholder concepts. This article willexplain about the roles and relations of stakeholders in managing RPTRAKalijodo, also the implications of the relation between stakeholders inmanaging that RPTRA. Partnerships between stakeholders that involved inRPTRA Kalijodo include the division of roles, cooperation, and collaborationbetween the local government and the surrounding society as an effort tomanage the RPTRA Kalijodo. The existence of that relation can be apartnership between stakeholders that involved, so the management of theRPTRA can run optimally and RPTRA Kalijodo can be utilized by the society.